SPARC, a phase-I trial of pre‐operative, margin intensified, stereotactic body radiation therapy for pancreatic cancer. (February 2021) - Holyoake, Daniel L.P.; Robinson, Maxwell; Silva, Michael; Grose, Derek; McIntosh, David; Sebag-Montefiore, David; Radhakrishna, Ganesh; Mukherjee, Somnath; Hawkins, Maria A.
Highlights: Prospective study of pre-operative margin intensified SBRT in borderline resectable pancreatic cancer. All SBRT was completed, dose was escalated one level without encountering DLT. Few patients had resection after SBRT, suitability of treatments combination is difficult to appraise. Abstract: Background and purpose: Following resection of pancreatic cancer, risk of positive margins and local recurrence remain high, especially for borderline-resectable pancreatic cancer (BRPC). We aimed to establish the maximum tolerated dose of a margin-intensified five-fraction stereotactic body radiotherapy (SBRT) regimen designed to treat the region at risk. Materials and methods: We conducted a prospective multicentre phase-1 rolling-six dose-escalation study. BRPC patients received pre-operative SBRT, with one dose to the primary tumour and an integrated boost to the region where tumour was in contact with vasculature. Four dose-levels were proposed, with starting dose 30 Gy to primary PTV and 45 Gy to boost volume (PTV_R), in five daily fractions. Primary endpoint was maximum tolerated dose (MTD), defined as highest dose where zero of three or one of six patients experienced dose-limiting toxicity (DLT). Results: Twelve patients were registered, eleven received SBRT. Radiotherapy was well tolerated with all treatment completed as scheduled. Dose was escalated one level up from starting dose without encountering any DLT (prescribed 32.5 Gy PTV, 47.5 Gy PTV_R). Nine serious adverse reactions or events occurred (seven CTCAE Grade 3, two Grade 4). Two patients went on to have surgical resection. Median overall survival for SBRT patients was 8.1 months. The study closed early when it was unable to recruit to schedule. Conclusion: Toxicity of SBRT was low for the two dose-levels that were tested, but MTD was not established. Few patients subsequently underwent resection of pancreatic tumour after SBRT, and it is difficult to draw conclusions regarding the safety or toxicity of these therapies in combination.